2004
DOI: 10.5483/bmbrep.2004.37.2.139
|View full text |Cite
|
Sign up to set email alerts
|

An Important Role of Nrf2-ARE Pathway in the Cellular Defense Mechanism

Abstract: The antioxidant responsive element (ARE) is a cis-acting regulatory element of genes encoding phase II detoxification enzymes and antioxidant proteins, such as NAD(P)H: quinone oxidoreductase 1, glutathione S-transferases, and glutamate-cysteine ligase. Interestingly, it has been reported that Nrf2 (NF-E2-related factor 2) regulates a wide array of ARE-driven genes in various cell types. Nrf2 is a basic leucine zipper transcription factor, which was originally identified as a binding protein of locus control r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
456
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 554 publications
(468 citation statements)
references
References 25 publications
7
456
1
3
Order By: Relevance
“…Indeed, metallothionein and HO-1 are among a group of Phase II detoxification enzymes and antioxidant proteins that function as a cellular defense mechanism against oxidative stress [39,40]; the expression of HO-1 in response to ROS is regulated by the interaction of transcription factor Nrf-2 with ARE sequences in the promoter regions of their respective genes [36]. Since MAP kinases are known to be involved in the activation of Nrf-2 [31], we examined whether gallium nitrate was signaling through this pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, metallothionein and HO-1 are among a group of Phase II detoxification enzymes and antioxidant proteins that function as a cellular defense mechanism against oxidative stress [39,40]; the expression of HO-1 in response to ROS is regulated by the interaction of transcription factor Nrf-2 with ARE sequences in the promoter regions of their respective genes [36]. Since MAP kinases are known to be involved in the activation of Nrf-2 [31], we examined whether gallium nitrate was signaling through this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the induction of HO-1 gene expression by MAP kinases is regulated through the activity of Nrf2, a basic leucine zipper transcription factor that interacts with antioxidant response elements (AREs) in the promoter region of the HO-1 gene [31,36]. Under basal conditions, Nrf2 is sequestered in the cytoplasm bound to KEAP-1 (Kelch-like ECHassociating protein 1) which targets it for proteasomal degradation [36].…”
Section: Gallium-induced Upregulation Of Ho-1 Involves Map Kinase P38mentioning
confidence: 99%
See 1 more Smart Citation
“…To combat this omnipresent oxidative stress, animal cells have evolved an endogenous antioxidant response. Nuclear factor (erythroid-derived 2) (NF-E2)-related factor 2 (Nrf2), is the key regulator of antioxidant response genes, making it an essential player in this endogenous cellular antioxidant response 1,2,3,4,5,6,7 ). Nrf2 is a member of the Cap 'n' Collar family of transcription factors, which includes Nrf1, Nrf3, p45, Bach1, and Bach2 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 is a member of the Cap 'n' Collar family of transcription factors, which includes Nrf1, Nrf3, p45, Bach1, and Bach2 2 ). Nrf2 binds the antioxidant responsive element (ARE), also known as the electrophile response element (EpRE)), a cis-acting regulatory element found in the 5′-flanking region of genes encoding enzymes for antioxidant production and of other Nrf2 target genes 2,3,8 ). Genes regulated by Nrf2 include heme oxygenase-1 (HO-1), ubiquitin/PKC-ζ-interacting protein A170, glutathione S-transferases (GST), NAD(P)H quinone oxidoreductase (NQO1), peroxiredoxin 1, catalasc, glutathione peroxidase, superoxide dismutase (SOD), and thioredoxin 1,4,9,10,11,12 ).…”
Section: Introductionmentioning
confidence: 99%